Reymont na Balu Prasy - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article discusses an unpublished short manuscript by Władysław Stanisław Reymont. A note placed by the author of The Peasants on a ball ticket from 1922 constitutes a starting point for the reconstruction of a minor, although particularly interesting, episode from the late period in the artist’s life.